2021
DOI: 10.1186/s12864-021-07538-w
|View full text |Cite
|
Sign up to set email alerts
|

Unique adaptations in neonatal hepatic transcriptome, nutrient signaling, and one-carbon metabolism in response to feeding ethyl cellulose rumen-protected methionine during late-gestation in Holstein cows

Abstract: Background Methionine (Met) supply during late-pregnancy enhances fetal development in utero and leads to greater rates of growth during the neonatal period. Due to its central role in coordinating nutrient and one-carbon metabolism along with immune responses of the newborn, the liver could be a key target of the programming effects induced by dietary methyl donors such as Met. To address this hypothesis, liver biopsies from 4-day old calves (n = 6/group) born to Holstein cows fed a control or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 169 publications
0
11
0
Order By: Relevance
“…However, work with sheep receiving a diet with marginal levels of methyl donors in the periconceptional period demonstrated marked alterations in DNA methylation (i.e., an epigenetic mark) in the fetal liver along with altered innate immune and glucose-insulin responses of the offspring at 22 mo of age ( Sinclair et al, 2007 ). In a recent study, it was demonstrated that enhanced post-ruminal supply of methionine in late-pregnant dairy cows not only led to greater calf birth weight ( Alharthi et al, 2018 ), but also marked alterations in immunometabolic networks in the calf liver including downregulation of inflammatory and antioxidant signaling pathways along with fatty acid oxidation and gluconeogenesis ( Palombo et al, 2021 ) ( Figure 3 ). It was noteworthy, however, that these calves had an overall upregulation of immune system pathways, which together suggested a more mature capacity to respond to immune challenges ( Palombo et al, 2021 ).…”
Section: Environmental Regulation Of Immunometabolic Networkmentioning
confidence: 99%
“…However, work with sheep receiving a diet with marginal levels of methyl donors in the periconceptional period demonstrated marked alterations in DNA methylation (i.e., an epigenetic mark) in the fetal liver along with altered innate immune and glucose-insulin responses of the offspring at 22 mo of age ( Sinclair et al, 2007 ). In a recent study, it was demonstrated that enhanced post-ruminal supply of methionine in late-pregnant dairy cows not only led to greater calf birth weight ( Alharthi et al, 2018 ), but also marked alterations in immunometabolic networks in the calf liver including downregulation of inflammatory and antioxidant signaling pathways along with fatty acid oxidation and gluconeogenesis ( Palombo et al, 2021 ) ( Figure 3 ). It was noteworthy, however, that these calves had an overall upregulation of immune system pathways, which together suggested a more mature capacity to respond to immune challenges ( Palombo et al, 2021 ).…”
Section: Environmental Regulation Of Immunometabolic Networkmentioning
confidence: 99%
“…PPAR), which can affect metabolism in tissues such as the liver (Sauerwein and Häußler 2016). It is now more apparent that TF and target gene networks work in conjunction to alter physiological pathways, not only in the mature animal (Shahzad et al 2014), but also in response to altering the nutrition of the mother during pregnancy (Namous et al 2018;Palombo et al 2021; Table 2).…”
Section: Transcription-factor Network and Nutrigenomicsmentioning
confidence: 99%
“…the ChIP-X Enrichment Analysis 3 (ChEA3) transcriptionfactor enrichment analysis tool (Keenan et al 2019). Its use in a recent nutrigenomics experiment dealing with RNA sequencing data from liver of neonatal calves born to cows fed normal or greater amounts of methionine (a methyl donor) during the last 30 days of pregnancy led to identification of 72 TF that had statistically significant associations with 568 differentially expressed genes (Palombo et al 2021). Among the TF identified were some with known nutrigenomic potential (Table 1), e.g.…”
Section: Transcription-factor Network and Nutrigenomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In sheep fed purified diets limited in cobalt and sulfur (thereby limiting the rumen biosynthesis of vitamin B 12 and methionine, respectively) from −60 to +6 days relative to insemination, the male offspring of methyl-donor-deficient ewes had an altered body composition by 22 months of age ( Sinclair et al, 2007 ). In dairy cows, supplementation of individual methyl donors or combinations of methionine, choline, folate, and vitamin B 12 has positively improved milk production, calf birth weight and height, amino acid flow to the calf, and nutrient profiles in milk ( Preynat et al, 2009a , b ; Batistel et al, 2017 ; Alharthi et al, 2018 ; Alharthi et al, 2019 ; Batistel et al, 2019 ; Palombo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%